Pemetaan Indeks Kerawanan Pemilu 2024 Perspektif Siyasah Dusturiyah - Agustin, Elva Astri; Rizal, Lutfi Fahrul; Saptaji, Aji (Postgraduate Program in Law, Universitas Pattimura, 2024)
Introduction: This research is motivated by the general election vulnerability that will occur in Bandung Regency in 2024. The Bandung Regency Election Vulnerability Index has reached 91.5 percent. The IKP measures include monitoring campaign violations, voting rights, income, money politics, ASN neutrality, hoax news.Purposes of the Research: The aim of this research is to analyze the vulnerabilities that occurred during the general election in Bandung Regency, highlighting the importance of comprehensive prevention and supervision efforts. With this mapping, stakeholders can focus more on monitoring, intervention and prevention efforts. The election vulnerability index also functions as a measuring tool to evaluate the effectiveness of the policies and strategies implemented in order to create clean, honest and fair elections.Methods of the Research: The research method used is qualitative with a descriptive type based on the focus of the study used, namely empirical research.Results of the Research: The results of the research show that there are potential vulnerabilities that occur in Bandung Regency. Bawaslu's function in preventing election violations includes identification and mapping of violations, coordination, monitoring and evaluation of election implementation. Bawaslu also coordinates with related government agencies and increases public participation in election supervision.